The Role of Job Satisfaction in Mediating the Influence of Transformational Leadership on Innovative Behavior in Employees of Pt. Xyz - Azriel Yuda Penalemen Tarigan; Ida Bagus Ketut Surya; I Gusti Made Suwandana (International Journal of Management Research and Economics, 2024)
The role of job satisfaction as a mediator of transformational leadership on employees' innovative behavior is crucial in the context of modern business competition. In the current era of globalization, competition between companies is increasingly strong, it requires companies to understand and optimize these factors to improve their performance and competitiveness. Therefore, this research aims to analyze the relationship between transformational leadership, job satisfaction, and employees' innovative behavior. This research was conducted at PT. XYZ , with a total sample of 60 employees determined based on saturation sampling. Data was collected through interviews and distributing questionnaires to research subjects. The data were analyzed using path analysis technique with SPSS. This research aims to analyze the mediating role of job satisfaction on the influence of transformational leadership on innovative behavior. The results of this research show that transformational leadership and job satisfaction significantly influence innovative behavior with a positive direction, transformational leadership significantly influences job satisfaction with a positive direction, and job satisfaction is able to mediate the influence of transformational leadership on innovative behavior as a partial . The implications of this research theoretically support the findings of previous research. The practical implications for PT. XYZ is to maintain innovative behavior, transformational leadership, and job satisfaction among its employees.